2021
DOI: 10.21470/1678-9741-2020-0299
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Chest Closure for Oversized Lung Allograft in Lung Transplantation: a Retrospective Analysis from Turkey

Abstract: Introduction The aim of this study was to evaluate the delayed chest closure (DCC) results in patients who underwent lung transplantation. Methods Sixty patients were evaluated retrospectively. Only bilateral lung transplantations and DCC for oversized lung allograft (OLA) were included in the study. Six patients who underwent single lung transplantation, four patients who underwent lobar transplantation, two patients who underwent retransplantation, and four patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…From literature search, a total of 8 studies (11)(12)(13)(14)(15)(16)(17)(18) were collected into the narrative review, the specific information of the collected articles were shown in Table S2. Of which 4 articles (11,13,14,17) were grouped by the delayed chest closure (DCC) execution and the other 4 articles (12,15,16,18) were grouped by the SSI occurred.…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From literature search, a total of 8 studies (11)(12)(13)(14)(15)(16)(17)(18) were collected into the narrative review, the specific information of the collected articles were shown in Table S2. Of which 4 articles (11,13,14,17) were grouped by the delayed chest closure (DCC) execution and the other 4 articles (12,15,16,18) were grouped by the SSI occurred.…”
Section: Research Resultsmentioning
confidence: 99%
“…From literature search, a total of 8 studies (11)(12)(13)(14)(15)(16)(17)(18) were collected into the narrative review, the specific information of the collected articles were shown in Table S2. Of which 4 articles (11,13,14,17) were grouped by the delayed chest closure (DCC) execution and the other 4 articles (12,15,16,18) were grouped by the SSI occurred. Two articles performed multivariate regression analysis (12,13) to determine the independent risk factors of SSI after lung transplantation and the other 6 articles compared the SSI rate in different patients population.…”
Section: Research Resultsmentioning
confidence: 99%